Prescription Drug Monitoring Program Use: National Dental PBRN Results. (April 2019) - McCauley, J.L.; Gilbert, G.H.; Cochran, D.L.; Gordan, V.V.; Leite, R.S.; Fillingim, R.B.; Brady, K.T.; ,
Introduction: The American Dental Association recommends that dentists use a prescription drug monitoring program (PDMP) prior to prescribing an opioid for acute pain management. Objective: The objective of this study was to examine dentists' experiences using their state PDMP, as well as the impact that state-mandated registration policies, mandated use policies, and practice characteristics had on the frequency with which dentists used their PDMP. Methods: We conducted a web-based cross-sectional survey among practicing dentist members of the National Dental Practice-Based Research Network ( n = 805). The survey assessed prescribing practices for pain management and implementation of risk mitigation strategies, including PDMP use. Survey data were linked with network Enrollment Questionnaire data to include practitioner demographics and practice characteristics. Results: Nearly half of respondents ( n = 375, 46.6%) reported having never accessed a PDMP, with the most common reasons for nonaccess being lack of awareness ( n = 214, 57.1%) and lack of knowledge regarding registration and use ( n = 94, 25.1%). The majority of PDMP users reported the program to be very helpful (58.1%) or somewhat helpful (31.6%). Dentists reported that PDMP use most often did not change their intended prescribing behavior (40.2%), led them not to prescribe an opioid (33.5%), or led them to prescribe fewer opioid doses (25.5%). Presence of a mandated use policy was significantly associated with increased frequency of PDMP use across a variety of situations, including prior to 1) prescribing any opioid for pain management, 2) issuing refills, 3) prescribing to new patients, and 4) prescribing to patients deemed high risk. Conclusion: Findings suggest that the majority of dentists find PDMPs helpful in informing their opioid-prescribing practices. Whereas the existence of a state-mandated use policy is a consistent predictor of dentists' PDMP use, outreach and education efforts may overcome key barriers to use identified in this study. Knowledge Transfer Statement: Findings from this national survey suggest that the majority of practicing dentists find PDMPs helpful in informing their opioid-prescribing practices; however, consistent PDMP use was not common. Whereas the existence of a state-mandated use policy is a consistent predictor of dentists' PDMP use, outreach and education efforts may overcome key barriers to use identified in this study.